2015
DOI: 10.1007/s10865-015-9642-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceived ambiguity as a barrier to intentions to learn genome sequencing results

Abstract: Many variants that could be returned from genome sequencing may be perceived as ambiguous—lacking reliability, credibility, or adequacy. Little is known about how perceived ambiguity influences thoughts about sequencing results. Participants (n=494) in an NIH genome sequencing study completed a baseline survey before sequencing results were available. We examined how perceived ambiguity regarding sequencing results and individual differences in medical ambiguity aversion and tolerance for uncertainty were asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…In the present study, individuals higher in optimism consistently reported better health on nearly all indices examined (with the exception of information seeking), even when controlling for SSA and sociodemographic factors. These results are consistent with prior research demonstrating benefits of optimism, including more active coping strategies (18, 19, 21), the ability to make prudent decisions about where to allocate one’s energies (57), and a reduction of the negative association of greater perceived ambiguity with lower intentions to learn potentially useful health information (58). Of course, optimism could have shown such a consistent association with outcomes because all outcomes were self-reported, and optimistic people may be more likely to evaluate these factors positively.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, individuals higher in optimism consistently reported better health on nearly all indices examined (with the exception of information seeking), even when controlling for SSA and sociodemographic factors. These results are consistent with prior research demonstrating benefits of optimism, including more active coping strategies (18, 19, 21), the ability to make prudent decisions about where to allocate one’s energies (57), and a reduction of the negative association of greater perceived ambiguity with lower intentions to learn potentially useful health information (58). Of course, optimism could have shown such a consistent association with outcomes because all outcomes were self-reported, and optimistic people may be more likely to evaluate these factors positively.…”
Section: Discussionsupporting
confidence: 90%
“…Individual characteristics that impact patient decision making about cancer screening and other medical interventions include one's tolerance of uncertainty or ambiguity (20)(21)(22). These constructs are closely related but have been distinguished in one analysis by a focus on current (ambiguity) and future health states (uncertainty) (23).…”
mentioning
confidence: 99%
“…These items also appear as outcomes in separate papers examining the role of individual differences in information avoidance on intentions to receive sequencing results (Taber et al, in press-a) optimism and risk perceptions on intentions to receive sequencing results (Taber et al, 2014), and ambiguity-related constructs and optimism on intentions to receive and share sequencing results (Taber et al, in press-b). Ancillary analyses including predictors from other manuscripts as covariates did not change the pattern of results.…”
mentioning
confidence: 99%